"Geometrical Land" Learning Media Design Material for Building Flat Side Spaces - Dian Mawarsari, Venissa; Larasati, Nur Baiti; Sulistyaningsih, Dwi (Hipotenusa: Journal of Mathematical Society, 2024)
Flat-sided space shapes are mathematical materials in the scope of geometry which discusses cubes, blocks, pyramids, and prisms. In this material, students often find it difficult to visualize objects and relate them to contextual problems. The role of teachers in overcoming these problems is certainly very necessary. One way that can be used is to utilize technology to create learning media. The application software that can be used is Articulate Storyline 3. This research aims to produce a learning media design for flat-sided building materials called "Geometrical Land". This research is part of development research which is limited to the development stage only. The stages carried out in this research include: needs analysis, media design, and media validation. The instrument used is a media expert and material expert validation sheet. There are 6 validators, consisting of 3 material expert validators and 3 media expert validators. The results of this development research are in the form of a percentage of the validation test scoring of material experts and media experts. The average percentage of validity test results for material experts was 86.18% and media experts showed 84.61%. This states that the learning media "Geometrical Land" is 'very valid' for use according to the conversion level of achievement.